Novel Streptomyces Sp. Reported in 2018: A Meta-Analysis - Aryal, Sagar; Neupane, Laxmi; Adhikari, Rameshwar; Regmi, Balmukunda; Koirala, Niranjan; Joshi, Dev R. (Anti-Infective Agents, 2021)
Streptomyces species are very well known for the production of antimicrobials and enzymes. The objective of this review was to search for the novel Streptomyces isolated in 2018 along with their characteristics and possible antimicrobial properties. The literature search was done according to the PRISMA flow diagram, where 28 research papers were eligible for the review. Data entry and analyses were performed using IBM SPSS Statistics version 25, while the phylogenetic tree was constructed using Geneious Prime Software. The data on general characteristics, biochemical as well as sugar fermentation tests, 16S rRNA gene sequence similarity and DNA-DNA hybridization relatedness were extracted from the research papers and summarized in tables and figures. The biosynthesis gene cluster (BGC) was identified using ‘antibiotics and secondary metabolite analysis shell-antiSMASH’, which showed the possibility of production of new antibiotics, antifungal and antitumor substances from the 28 novel Streptomyces isolated in 2018 which would contribute to the global effort to fight against growing multidrug-resistance.
Keywords: meta-analysis